What Are the Benefits of Data Sharing? Uniting Supply Chain and Platform Economy Perspectives - Henri Huttunen; Timo Seppälä; Ilkka Lähteenmäki; Juri Mattila (The Research Institute of the Finnish Economy (ETLA), 2019)
Data as a resource and data sharing enable competitive supply chains and present-day digital platform business models. The recipe for these competitive supply chains will no longer be contingent on how different companies contract to share data in their existing business networks but how these companies make these contracts available for the others in multisided markets. Advancing the availability of data sharing contracts has led to novel internal and external operational efficiencies and to new types of strategic opportunities. Data sharing is nothing new. Approximately 49% of the companies already share data with other companies. How has data sharing emerged between companies? What types of benefits have companies reached by sharing data? Those are the two research questions we are answering in this study. Additionally, we map the trajectory of data sharing technologies and their benefits for companies. External strategic opportunities cannot be reached unless the product, service and software architectures are modular; in addition, the boundary resources are not being considered by the companies. Finally, the tools for evaluating the value capture of indirect network effects is missing from widely accepted business case valuation methods. The question remains - what type of data resources can companies treat as proprietary or as shared?
Keywords: M21; O30; P49; 330; Data as a resource; Data sharing; Boundary resources; EDI-economy; API-economy; Network Effects; IHAN-project